Pengaruh Makroekonomi dan Mikroekonomi terhadap Return Saham dengan Intervening Kurs pada Sektor Finance di BEI Periode 2014-2018 - Riski Ardiyansyah; R.A Sista Paramita (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This research was to determine the effects of macroeconomic and microeconomic on stock return with the exchange rate as a mediating variable on finance sectors listed on the Indonesia stock exchange in 2014-2018. The data were obtained from the company's annual financial statements on www.idx.co.id. and www.bi.go.id., then being sorted using purposive sampling techniques. The samples were 56 companies from a total of 97 companies in the finance sectors listed in the Indonesia Stock Exchange in 2014-2018. This research is explanative with the path analysis model and analyzed using smartPLS 3.0. The results indicate that the exchange rate and PBV have significant positive effects on stock return, while inflation, BI rate, ROE, and PER do not affect the stock return. It because the investors are more interested in an investment that offers higher return such as the exchange rate and have a minor risk for being bankrupt. Inflation does affect the exchange rate. Testing the indirect effects of inflation on the stock return through the exchange rate shows the results have a significant positive effect.